SISTEM INFORMASI KINERJA DAN KENAIKAN JABATAN KARYAWAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) (STUDI KASUS: SEKOLAH INSAN TELADAN) - Asmarini; Rika Perdana Sari (ABEC Indonesia, 2021)
Yayasan Berkah Sejahtera Suluh Bangsaku (YBSSB) is an educational institution located in the city of Pekanbaru. Based on the results of questions and answers with YBSSB, the foundation annually assesses employee performance. In the process of employee performance appraisal, the foundation requires performance data from each employee. The results obtained from the employee performance appraisal will be used to determine the employee's promotion. However, the assessment data is still managed manually using paper and is not stored in the same place. So that the foundation has difficulty finding the required data. In addition, the foundation has difficulties in determining which employees will be given a promotion based on the results of employee performance appraisals. Therefore, a system was built that could assist the foundation in managing this data. Meanwhile, to determine employee promotion, the method is used Simple Additive Weighting (SAW). Based on the tests carried out, the preference value obtained using the same data, both manual calculation and system calculation, has the same final result 100%. The system built can assist YBSSB in assessing the performance of its employees and assisting in recommending employees for promotion.